Epistemological analysis of concept extrapolation as a method of creating a glossary - Olga Pashanova, Аndrey Korzhuev,; Antipin, Evgeniy; Sadykova, Al'bina; Ryazanova, Elena (Opción, 2020)
The study analyzes term creation in educational sciences and the transmission of its results into the segment of the theoretical humanitarian norm. Based on the representative content analysis of the pedagogical and scientific literature, positive and negative results of the extrapolation of various scientific concepts into educology are typified. As a result, the attempts to theoretically build educational science are substantially complicated by the problems of educological inductivism. In conclusion, the correctness is also complemented by the requirement of constructiveness; the meanings of well-known terms are being repeated and it is included in the scientific perspective reflection.